Transformasi Pendidikan Bahasa Inggris dan Matematika: Pendampingan Kebutuhan Sekolah Menengah untuk Meningkatkan Relevansi dan Minat Mahasiswa di IAIN Takengon - Delfia Herwanis; Maulida Maulida; Addahri Hafidz Awlawi (Lembaga Pengembangan Kinerja Dosen, 2024)
The focus of this study is the transformation of English and Mathematics education at the State Islamic Institute (IAIN) Takengon. Higher education at IAIN Takengon faces challenges in increasing student interest, especially in English and Mathematics study programs. Students believe that mathematics and English skills are not important for career success. This is a common problem in many universities in Indonesia. By focusing on the analysis of high school needs, this study attempts to address the problem. The results of the analysis indicate that IAIN Takengon programs can be tailored to meet the specific needs of English and Mathematics students. As part of the solution, IAIN Takengon students engage directly with high school students and gain hands-on experience in mentoring and teaching. To determine the needs of high schools, an analysis of the study program curriculum, interviews with teachers and students, and observations were conducted. The results of the study indicate that the English and Mathematics curriculum needs to be improved specifically, and the program should be more related to students' real lives. Case studies and qualitative methods are considered effective in collecting contextual data and providing in-depth insights into the state of education at IAIN Takengon. Other practical recommendations include curriculum adjustments, creating learning materials that are more in line with industry needs, and training teachers to implement innovative teaching methods.